Laparoscopic Total Gastrectomy in Elderly Patients (≥70 Years) with Gastric Carcinoma: A Retrospective Study - Jung, Hong Sung (J Gastric Cancer, 2015)
PURPOSE: To compare the surgical outcomes of laparoscopic total gastrectomy between elderly and non-elderly patients. MATERIALS AND METHODS: Between 2008 and 2015, a total of 273 patients undergoing laparoscopic total gastrectomy for gastric carcinoma were divided into two age groups: elderly (≥70 years, n=71) vs. non-elderly (<70 years, n=172). Postoperative outcomes, including length of hospital stay, morbidity, and mortality were compared between the groups. RESULTS: The elderly group showed a significantly higher rate of comorbidities and American Society of Anesthesiologists scores than those in the non-elderly group. No significant differences were found with respect to lymphadenectomy or combined organ resection between the groups. After surgery, the elderly group showed a significantly higher incidence of grade III and above complications than the non-elderly group (15.5% vs. 4.1%, P=0.003). Among the complications, anastomosis leakage was significantly more common in the elderly group (9.9% vs. 2.9%, P=0.044). Univariate and multivariate analyses showed that old age (≥70 years) was an independent risk factor (odds ratio=4.42, 95% confidence interval=1.50~13.01) for postoperative complications of grade III and above. CONCLUSIONS: Elderly patients are more vulnerable to grade III and above complications after laparoscopic total gastrectomy than non-elderly patients. Great care should be taken to prevent and monitor the development of anastomosis leakage in elderly patients after laparoscopic total gastrectomy.